PNA binding to the non-template DNA strand interferes with transcription, suggesting a blockage mechanism mediated by R-loop formation - Belotserkovskii, Boris P. (Mol Carcinog, 2014)
Peptide Nucleic Acids (PNAs) are artificial DNA mimics with superior nucleic acid binding capabilities. T7 RNA polymerase transcription upon encountering PNA bound to the non-template DNA strand was studied in vitro. A characteristic pattern of blockage signals was observed, extending downstream from the PNA binding site, similar to that produced by G-rich homopurine-homopyrimidine sequences and likely caused by R-loop formation. Since blocked transcription complexes in association with stable R-loops may interfere with replication and in some cases trigger apoptosis, targeted R-loop formation might be employed to inactivate selected cells, such as those in tumors, based upon their unique complement of expressed genes.